Electronics Student Worksheet Based on Higher Order Thinking Skills for Grade IV Elementary School - Rahayu, Sri; Ladamay, Iskandar; Wiyono, Bambang Budi; Susanti, Romia Hari; Purwito, Naufal Rafif (Universitas Pendidikan Ganesha, 2021)
The Student Worksheets (LKPD) available so far only contain black and white writing. In addition, the pictures and questions presented did not attract students' interest in learning. Therefore, it is necessary to develop LKPD that can attract students' learning interests. This study aims to develop Electronic LKPD (E-LKPD) thematic learning based on Higher Order Thinking Skills (HOTS). This research is a type of development research (RnD). The development model uses the ADDIE model which consists of the Analysis, Design, Development, Implementation, Evaluation stages. The E-LKPD product that has been developed is then tested on validators, teachers, and students to determine the effectiveness of its use. Data analysis techniques were carried out descriptively, qualitatively, and quantitatively. Validation is carried out by three validators, namely content, material, and language validators. The research instrument is a teacher response questionnaire for practicality and a student response questionnaire for attractiveness. The average validation result of media experts is 3.6 with the